2007
DOI: 10.1063/1.2772756
|View full text |Cite
|
Sign up to set email alerts
|

Fourier plasmonics: Diffractive focusing of in-plane surface plasmon polariton waves

Abstract: An in-plane Fresnel zone plate (FZP) for focusing surface plasmon polariton (SPP) fields has been designed, fabricated, and tested. The fabricated device consists of 400nm tall by 5μm wide amorphous Si-based SPP FZP on an Al film integrated with a pair of two-dimensional nanohole arrays for excitation of the incident and detection of the diffracted SPP fields. Diffracted SPP fields from each Fresnel zone constructively interfere at the expected focal point to produce focusing with threefold intensity enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 19 publications
0
63
0
Order By: Relevance
“…Indeed, it provides a framework to develop surface plasmon Fourier optics. Similar representations have been postulated as ansatz to surface plasmons interferences 27 , propagation along a stripe 5 or focussing 18 . The framework introduced above provides a rigorous derivation of the form of the surface plasmon field valid in a region with no sources.…”
Section: B Surface Plasmon Field Representation With a Real Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it provides a framework to develop surface plasmon Fourier optics. Similar representations have been postulated as ansatz to surface plasmons interferences 27 , propagation along a stripe 5 or focussing 18 . The framework introduced above provides a rigorous derivation of the form of the surface plasmon field valid in a region with no sources.…”
Section: B Surface Plasmon Field Representation With a Real Frequencymentioning
confidence: 99%
“…It is well-known that a finite size beam propagating in a vacuum has to be described in terms of a linear superposition of plane waves. Differents ansatz, often neglecting polarization, have been used in the litterature to address this question 5,18,27 . One of the goals of this paper is to derive a rigorous representation for the surface plasmon field.…”
Section: Introductionmentioning
confidence: 99%
“…SPPs are electronic-electromagnetic modes sustained at an appropriate metallic/dielectric interface wherein the field reaches its maximum intensity at the surface of the metal. [1][2][3] Extensive studies have reported on 2D optical elements based on SPPs, including SPP scattering, [4][5][6] Bragg mirrors, 7,8 lenses, [9][10][11][12][13] interferometers and resonators. 14,15 However, 2D optics based on SPPs are intrinsically limited by absorption losses due to metals, which reduce the propagation length of SPPs.…”
Section: Introductionmentioning
confidence: 99%
“…Various schemes have been proposed [8][9][10][11][12] but previous attempts in planar nanostructured materials have demonstrated a poor efficiency because of the difficulty to couple light into the nanostructures [13] used to generate SPP. Optical fiber tapers confine adiabatically light to the diffraction limit and provide an extremely regular field distribution within a relatively small area.…”
Section: Introductionmentioning
confidence: 99%